Quantitative assessment of artefacts and identification of gaps in prosthetic crowns: a comparative in vitro study between periapical radiography and CBCT images - Mauad, Leticia Queiroz; Teixeira Doriguetto, Paulo Victor; Almeida, Daniela de; Castilho Fardim, Karolina Aparecida [UNESP]; Machado, Alessiana Helena; Devito, Karina Lopes (British Inst Radiology, 2021)
Objectives: To evaluate, in an in vitro study, the quantity of artefacts generated by two different restorative materials, and to determine the diagnostic accuracy of cone beam CT (CBCT) scans and periapical radiographs in identifying gaps in prosthetic crowns. Methods: A total of 30 teeth restored with metal-ceramic (n = 15) and all-ceramic (n = 15) crowns, properly adapted and with 0.30- and 0.50 mm gaps, underwent CBCT exams (with voxel sizes of 0.25 and 0.30 mm) and periapical radiographs. The artefacts generated by two different crowns were quantified and compared by the Mann-Whitney test. In addition, five examiners evaluated the presence or absence of gaps in periapical radiographs and CBCT images. The accuracy of tests was determined by the area under the receiver operatring characteristic curve and these values were compared by using the Kruskal-Wallis test. Results: There was no significant difference in artefact values between the different restorative materials and the different resolutions of CBCT images. Regarding the accuracy of the tests evaluated, periapical radiography and CBCT with voxel size 0.25 mm showed the best performance for smaller gaps (0.30 mm). For larger gaps (0.50 mm), all exams tested showed the same performance. Conclusions: Periapical radiography was still the most cost-beneficial method for the diagnosis of maladaptation in dental restorations. CBCT exams did not improve accuracy in detecting gaps in prosthetic crowns.
Keywords: cone beam computed tomography; artefacts; ceramics; metal ceramic alloys; dental marginal adaptation